Improving English Teacher Competence in Implementing Differentiated Instruction Online Learning Model to Accommodate Various Student Learning Styles - Nurjamin, Lucky Rahayu; Hermawan, Toto; Anila, Aan; Yuliana, Lina; Kencanawati, Kania Dewi; Fitryani, Enung; Suardi, Dodi; Lisyanti, Dedeh; Gustina, Nida Nur; Herlina, Herlina; Nurlaila, Hera; Erniyati, Erniyati; Purwanti, Yani; Sholihah, Kiah Nur (Indonesian Journal of Community Empowerment (IJCE), 2024)
This Community Service activity aimed to enhance the competency of 37 English teachers in Garut Regency in applying the Differentiated Instruction (DI) model in online learning to accommodate diverse student learning styles, aligned with the Merdeka Belajar Curriculum. The activity was conducted on Sunday, April 14, 2024, at Aula Gedung G, IPI Garut, through interactive workshops and practical simulations. The results showed a significant increase in teachers' conceptual understanding and practical skills in designing differentiated learning. The strong positive response from teachers indicated that DI is not just an option but an urgent necessity for creating an inclusive and effective learning environment amidst student diversity. This activity recommends the need for continuous mentoring, further module development, and the establishment of professional learning communities to ensure sustained and optimal DI implementation.